Space warfare strategy, principles, and policy - Klein, John J. (Space power and politics, 2006)
Considers military space strategy within the context of the land and naval strategies of the past. This book shows why many such strategies unintentionally lead to overemphasizing the importance of space-based offensive weaponry and technology. It is of interest to students and scholars of military and strategic studies